2020
DOI: 10.1021/acs.jpclett.0c00221
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide Sensitizers for Large Anti-Stokes Shift Near-Infrared-to-Visible Triplet–Triplet Annihilation Photon Upconversion

Abstract: The upconversion of near-infrared (NIR) to visible (vis) photons is of interest for display technologies and energy conversion. Although triplet–triplet annihilation (TTA) offers a mechanism for upconversion that works efficiently at low incident irradiance flux densities, current strategies for NIR–vis upconversion based on TTA have fundamental limitations. Herein, we report a strategy for NIR–vis TTA based on lanthanide-containing complexes to sensitize the upconversion. We demonstrate a β-diketonate complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 27 publications
(42 reference statements)
0
49
0
Order By: Relevance
“…Upon excitation with 980 nm laser, the Yb-L/rubrene couple in deoxygenated deuterated tetrahydrofuran showed energy upconversion with DE UC = 0.95 eV (980 nm to 559 nm) and F UC of o 0.5%. 41 However, besides the advantage of clear optical window, several limitations of Yb-L sensitizer were also highlighted such as poor F UC , high excitation intensity and requirement of deuterated solvents. The deuterated solvent was required to avoid nonradiative deactivation by multiphoton relaxation via energy transfer to vibrational overtones of high-energy, highly anharmonic oscillators (mostly stretching modes of X-H moieties with X = O, N, C) in the vicinity of the metal.…”
Section: Chem Soc Rev Tutorial Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Upon excitation with 980 nm laser, the Yb-L/rubrene couple in deoxygenated deuterated tetrahydrofuran showed energy upconversion with DE UC = 0.95 eV (980 nm to 559 nm) and F UC of o 0.5%. 41 However, besides the advantage of clear optical window, several limitations of Yb-L sensitizer were also highlighted such as poor F UC , high excitation intensity and requirement of deuterated solvents. The deuterated solvent was required to avoid nonradiative deactivation by multiphoton relaxation via energy transfer to vibrational overtones of high-energy, highly anharmonic oscillators (mostly stretching modes of X-H moieties with X = O, N, C) in the vicinity of the metal.…”
Section: Chem Soc Rev Tutorial Reviewmentioning
confidence: 99%
“…The deuterated solvent was required to avoid nonradiative deactivation by multiphoton relaxation via energy transfer to vibrational overtones of high-energy, highly anharmonic oscillators (mostly stretching modes of X-H moieties with X = O, N, C) in the vicinity of the metal. 41 Even after being highly prone to photo-degradation, rubrene has been the main annihilator in most of the NIR to Vis TTA-UC systems. Kazlauskas's research group investigated the low F UC of metallophthalocyanine sensitized rubrene systems based on the subsequent energy transfer steps.…”
Section: Chem Soc Rev Tutorial Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Examples of sensitizers include coordination complexes, due to their strong absorption bands and high triplet yield via intersystem crossing, 6,[8][9][10][11][12][13][14][15] as well as colloidal quantum dots (QDs), [16][17][18][19][20][21][22][23] metal-halide perovskite lms and nanocrystals, [24][25][26] and materials containing lanthanide atoms. 5,27 Triplet fusion (TF) occurs when the energy from two or more triplet-excited acceptors are combined to yield a higher-energy excited state, which may generate a spin-singlet excitation capable of emitting a photon. 1,6,9,28,29 Importantly, it was recently demonstrated that triplet-fusion upconversion can enable photochemical transformations using incident long-wavelength light at low uences appropriate for tissue penetration.…”
Section: Introductionmentioning
confidence: 99%